Relationships between force-time curve variables and jump height during countermovement jumps in young elite volleyball players - Sarvestan, J.; Cheraghi, M.; Sebyani, M.; Shirzad, E.; Svoboda, Z. (Acta Gymnica, 2018)
Background: The importance of vertical jumps has been extensively recognised in sports. Furthermore, the main indicator of success in vertical jumps is the attained height, however, there is lack of knowledge on how the eccentric and concentric force-time curve variables affect the jump height.